Pengembangan Teknologi Informasi di Dunia Kesehatan dan Pendidikan - Katulistiwa, Nariyah Koriyota; Nata Dirgantara Putra Wahdana; Nitya Nabilah Nariswari; Nur Diana Hamidah; Nur Mufidah (POLTEKKES KEMENKES YOGYAKARTA, 2022)
The development of technology and information is common in the digital age. Online media as a form of sophistication of information and communication technology plays a big role in human life, one of which is in improving health services. Based on the background above researchers are interested in conducting this study entitled